Characterization of Long Non-coding RNAs Modified by m6A RNA Methylation in Skeletal Myogenesis - Xie, Shu-Juan; Tao, Shuang; Diao, Li-Ting; Li, Pan-Long; Chen, Wei-Cai; Zhou, Zhi-Gang; Hu, Yan-Xia; Hou, Ya-Rui; Lei, Hang; Xu, Wan-Yi; Chen, Wen-Jie; Peng, Yan-Wen; et al. (Frontiers in cell and developmental biology, 2021)
Proper development of mammalian skeletal muscle relies on precise gene expression regulation. Our previous studies revealed that muscle development is regulated by both mRNA and long non-coding RNAs (lncRNAs). Accumulating evidence has demonstrated that N 6 -methyladenosine (m 6 A) plays important roles in various biological processes, making it essential to profile m 6 A modification on a transcriptome-wide scale in developing muscle. Patterns of m 6 A methylation in lncRNAs in developing muscle have not been uncovered. Here, we reveal differentially expressed lncRNAs and report temporal m 6 A methylation patterns in lncRNAs expressed in mouse myoblasts and myotubes by RNA-seq and methylated RNA immunoprecipitation (MeRIP) sequencing. Many lncRNAs exhibit temporal differential expression, and m 6 A-lncRNAs harbor the consensus m 6 A motif “DRACH” along lncRNA transcripts. Interestingly, we found that m 6 A methylation levels of lncRNAs are positively correlated with the transcript abundance of lncRNAs. Overexpression or knockdown of m 6 A methyltransferase METTL3 alters the expression levels of these lncRNAs. Furthermore, we highlight that the function of m 6 A genic lncRNAs might correlate to their nearby mRNAs. Our work reveals a fundamental expression reference of m 6 A-mediated epitranscriptomic modifications in lncRNAs that are temporally expressed in developing muscle.